Dielectric relaxation and electrical conduction mechanism in A2HoSbO6 (A=Ba, Sr, Ca) Double Perovskite Ceramics: An impedance spectroscopic analysis. (March 2017) - Halder, Saswata; Dutta, Alo; Sinha, T.P.
Abstract: The AC electrical properties of polycrystalline double perovskite oxides A2 HoSbO6 (A=Ba, Sr, Ca; AHS) synthesized by solid state reaction technique has been explored by using impedance spectroscopic studies. The Rietveld refinement of the room temperature X-ray diffraction data show that Ba2 HoSbO6 (BHS) has cubic phase and Sr2 HoSbO6 (SHS) and Ca2 HoSbO6 (CHS) crystallize in monoclinic phase. The samples show significant frequency dispersion in their dielectric properties. The polydispersive nature of the relaxation mechanism is explained by the modified Cole-Cole model. The scaling behavior of dielectric loss indicate the temperature independence of the relaxation mechanism. The magnitude of the activation energy indicates that the hopping mechanism is responsible for carrier transport in AHS. The frequency dependent conductivity spectra follow the double power law. Impedance spectroscopic data presented in the Nyquist plot (Z" versus Z′) are used to identify an equivalent circuit along with to know the grain, grain boundary and interface contributions. The constant phase element (CPE) is used to analyze the experimental response of BHS, SHS and CHS comprehending the contribution of different microstructural features to the conduction process. The temperature dependent electrical conductivity shows a semiconducting behavior. Highlights: Synthesis and structural refinement of double perovskite A2 HoSbO6 (A= Ba, Sr, Ca) are performed. Dielectric studies shows relaxation in the ac transport properties of A2 HoSbO6 . Conduction mechanism varies from nearest neighbor to variable range hopping. Major contribution to the conduction process comes from grain boundaries. The Nyquist plots are analyzed using an electrical R-CPE equivalent circuit.